Аutomated system of commercial electric power accounting (Visnyk NTUU KPI Seriia - Radiotekhnika Radioaparatobuduvannia, 2010)
This article discusses the basic principles of electric power automated accounting systems. It is highlighted key trends and challenges in designing such systems.